Naringenin Protects against Acute Pancreatitis in Two Experimental Models in Mice by NLRP3 and Nrf2/HO-1 Pathways - Yong Li; Yiyuan Pan; Lin Gao; Jingzhu Zhang; Xiaochun Xie; Zhihui Tong; Baiqiang Li; Gang Li; Guotao Lu; Weiqin Li (Mediators of Inflammation)
Background. Naringenin (Nar) is a type of flavonoid and has been shown to have anti-inflammatory and antioxidative properties. However, the effects of Nar on acute pancreatitis (AP) have not been well studied. In this study, we aimed to investigate the function of Nar in a mouse model of AP. Methods. Mild acute pancreatitis (MAP) was induced by caerulein (Cae), and severe acute pancreatitis (SAP) was induced by L-arginine in mice. Nar was administered intraperitoneally at doses of 25, 50, or 100 mg/kg following MAP induction and at a dose of 100 mg/kg following SAP induction. The serum levels of cytokines, lipase, and amylase were determined, and pancreatic and pulmonary tissues were harvested. Results. The serum levels of amylase, lipase, and cytokines were significantly decreased in both MAP and SAP models after Nar treatment. The malondialdehyde (MDA) levels of the pancreatic tissue was significantly reduced in both MAP and SAP after Nar treatment. In contrast, glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST), total sulfhydryl (T-SH), and non-proteinsulthydryl (NP-SH) were markedly increased in both MAP and SAP after Nar treatment. The injury in pancreatic and pulmonary tissues was markedly improved as evidenced by the inhibited expression of myeloperoxidase, nod-like receptor protein 3, and interleukin 1 beta as well as the enhanced expression of nuclear factor erythroid 2-related factor 2/heme oxygenase-1 in pancreatic tissues. Conclusions. Nar exerted protective effects on Cae-induced MAP and L-arginine-induced SAP in mice, suggesting that Nar may be a potential therapeutic intervention for AP.